2002
DOI: 10.14356/kona.2002018
|View full text |Cite
|
Sign up to set email alerts
|

Performance and Cost-Effectiveness of Ferric and Aluminum Hydrous Metal Oxide Coating on Filter Media to Enhance Virus Removal

Abstract: Coating sand and granular activated carbon with iron aluminum hydroxides changed the zeta potential of these filtration media from negative to positive at pH 6-9, while also significantly improving removal of viruses (MS2, PRD1, Polio1

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 8 publications
1
6
0
Order By: Relevance
“…No log reduction was observed for MS2 bacteriophages, which is consistent with previous studies that reported no reduction [47] or low reduction [51][52][53] of viruses and bacteriophages using granular activated carbon filters. Many studies suggested that the deposition of microbial particles, such as viruses, is inconsistent with the classical colloid filtration theory (CFT) due to the presence of Derjaguin-Landau-Verwey-Overbeek (DLVO) repulsive interactions [54][55][56], causing different colloidal behaviour and unfavourable conditions for deposition, as the case herein.…”
Section: Reduction Of Pathogen Surrogatessupporting
confidence: 91%
“…No log reduction was observed for MS2 bacteriophages, which is consistent with previous studies that reported no reduction [47] or low reduction [51][52][53] of viruses and bacteriophages using granular activated carbon filters. Many studies suggested that the deposition of microbial particles, such as viruses, is inconsistent with the classical colloid filtration theory (CFT) due to the presence of Derjaguin-Landau-Verwey-Overbeek (DLVO) repulsive interactions [54][55][56], causing different colloidal behaviour and unfavourable conditions for deposition, as the case herein.…”
Section: Reduction Of Pathogen Surrogatessupporting
confidence: 91%
“…38 Further testing is necessary to determine the level, if any, of such removal, as well as the extent to which chemical coatings or other enhancements to the filter media could result in sufficient virus removal or deactivation to protect communities from waterborne viral pathogens. 39 The results from this trial suggest that household-based ceramic gravity water filters may be an effective intervention in improving microbial water quality and reducing diarrheal disease among a susceptible population. In this respect, ceramic filtration may be another useful tool in helping the most vulnerable populations secure the health benefits of safe drinking water.…”
Section: Discussionmentioning
confidence: 88%
“…The internal walls of the columns were brushed to render them rough using sandpaper to reduce risk of short circuiting. The filter media were packed into columns in accordance with the method previously described (Scott et al, 2002). Specifically, the filter media was wetted with 10% deionised water (to avoid re-suspension) and added incrementally (every 50 mm) through the top of the columns.…”
Section: Laboratory Column Testmentioning
confidence: 99%